Bioactive Secondary Metabolites from Schizogyne sericea (Asteraceae) Endemic to Canary Islands. Issue 7 (4th July 2016) - Venditti, Alessandro; Bianco, Armandodoriano; Muscolo, Camilla; Zorzetto, Christian; Sánchez‐Mateo, Candelaria C.; Rabanal, Rosa M.; Quassinti, Luana; Bramucci, Massimo; Damiano, Silvia; Iannarelli, Romilde; Lupidi, Giulio; Papa, Fabrizio; et al.
Abstract : Schizogyne sericea (Asteraceae) is a halophytic shrub endemic to the Canary Islands and traditionally employed as analgesic, astringent, anti‐inflammatory, and vulnerary. A comprehensive phytochemical investigation was conducted on the flowering aerial parts by analyzing both essential oil constituents and polar compounds. The essential oil was dominated by p ‐cymene, with the noteworthy occurrence of β ‐pinene and thymol esters. From the EtOH extract, eight compounds were isolated and structurally elucidated. Essential oil, polar fractions, and isolates (2 ), (4 ), and (5 ) were separately in vitro assayed for antiproliferative activity on human tumor cell lines (A375, MDA‐MB 231, and HCT116) by MTT assay, for antioxidant potential by DPPH, ABTS, and FRAP assays, and for antimicrobial activity by the agar disk diffusion method. Results revealed that essential oil and compounds1 and2 exert a strong inhibition on tumor cells, and in some cases, higher than that of cisplatin. Fractions containing thymol derivatives (1 and2 ) and caffeoylquinic acid derivatives4 and5 displayed antioxidant activity comparable to that of Trolox, making S. sericea extract an interesting natural product with potential applications as preservative or in the treatment of diseases in which oxidative stress plays an important role. Abstract :